Physics of ankle injuries - Cross, R. (Medicine and Science in Tennis, 2004)
Concerning ankle injuries it is concluded that inventing better shoes based on the biomechanical/physical principles is unlikely to be very profitable. Such shoes would suit mainly top players competing on hard courts. Average players and many professionals make the mistake of wearing the same type of shoe on all surfaces. Top players don't ask how much shoes cost. They ask how much they will be paid to wear them.